Advances in free-energy-based simulations of protein folding and ligand binding. (February 2016) - Perez, Alberto; Morrone, Joseph A; Simmerling, Carlos; Dill, Ken A
Graphical abstract: Highlights: Molecular dynamics is reaching longer timescales faster than Moore's law's rate. Improved sampling algorithms, force fields and computers drive advances. At current rate of advance, many single domain proteins will be foldable in five years. Computed ligand binding affinities can be accurately compared with experiment. Force fields have improved to make prediction, and not only postdiction, possible. Abstract : Free-energy-based simulations are increasingly providing the narratives about the structures, dynamics and biological mechanisms that constitute the fabric of protein science. Here, we review two recent successes. It is becoming practical: first, to fold small proteins with free-energy methods without knowing substructures and second, to compute ligand–protein binding affinities, not just their binding poses. Over the past 40 years, the timescales that can be simulated by atomistic MD are doubling every 1.3 years — which is faster than Moore's law. Thus, these advances are not simply due to the availability of faster computers. Force fields, solvation models and simulation methodology have kept pace with computing advancements, and are now quite good. At the tip of the spear recently are GPU-based computing, improved fast-solvation methods, continued advances in force fields, and conformational sampling methods that harness external information.